Oncostatin M enhances the lengthening of sensory nerves and skin hypersensitivity - Ishikawa, Chie; Saito, Ryo; Suehiro, Masataka; Ishii, Kaori; Yanase, Yuhki; Kawaguchi, Tomoko; Uchida, Kazue; Yanagida, Nozomi; Numata, Tomofumi; Sasaki, Wataru; Kamigaki, Rina; Takeno, Sachio; et al. (Frontiers in Immunology, 2025)
BackgroundOncostatin M (OSM) is a cytokine that mediates inflammatory processes and is overexpressed in skin lesions of atopic dermatitis (AD). By amplifying neural responses to chemicals such as histamine, OSM increases sensitivity to pruritus. However, the morphological effects of OSM on peripheral sensory nerves and their subsequent impact on pruritus remain unclear. This study investigated OSM-induced peripheral nerve elongation, which may contribute to skin hypersensitivity.MethodsWe assessed neurite outgrowth using primary mouse dorsal root ganglion (DRG) cells treated with OSM, IL-31, or nerve growth factor. Next, we pre-treated the cells with inhibitors of downstream signaling pathways of OSM, including extracellular signal-regulated kinase (ERK), signal transducers and activator of transcription (STAT) 3, c-Jun N-terminal kinase (JNK), and p38, followed by OSM administration to measure neurite outgrowth. Furthermore, OSM receptor β-overexpressing cell lines were established by gene transfer into the DRG cell line, and nerve elongation was measured after OSM administration. In vivo studies involved OSM administration in mouse skin models. Immunofluorescence staining was used to evaluate nerve elongation. We examined whether OSM-infused mice had increased hypersensitivity to mechanical stimuli-induced pruritus. Various cytokine stimuli were applied to CD4+ T cells isolated from healthy humans to examine the conditions under which OSM production increases.ResultsOSM significantly induced neurite outgrowth in DRG cells and the effect of OSM surpassed the effects of IL-31 and nerve growth factor. The neurite outgrowth effect of OSM involved the JAK/STAT3, MEK/ERK, and p38/MAPK pathways. Compared to control cells, DRG cell lines that overexpressed OSM receptor β showed significantly enhanced neurite outgrowth upon OSM treatment. In vivo, OSM treatment increased nerve elongation in the mouse dermis. Behavioral assays in mice showed that OSM administration increased sensitivity to mechanical stimuli. IL-4 and TNFα increased OSM production in CD4+ T cells.ConclusionOSM induces neurite elongation and may contribute to skin hypersensitivity. This suggests the potential utilization of OSM as a therapeutic target for inflammatory skin diseases such as AD.